BNT162b2 Booster Vaccination Elicits Cross-Reactive Immunity Against SARS-CoV-2 Variants B.1.1.529 and B.1.617.2 in Convalescents of All Ages - Jahrsdörfer, Bernd; Proffen, Matthias; Scholz, Judith; Hägele, Janina; Ludwig, Carolin; Vieweg, Christiane; Grempels, Aline; Fabricius, Dorit; Lotfi, Ramin; Körper, Sixten; Adler, Guido; Schrezenmeier, Hubert (Frontiers in Immunology, 2022)
In this prospective observational cohort study we analyzed cellular and serological immune response parameters against SARS-CoV-2 and current variants of concern (VOC) in 147 COVID-19-convalescent and 39 COVID-19-naïve individuals before and after BNT162b2 booster vaccination. No significant differences regarding immunological response parameters were observed between younger and older individuals. Booster vaccination induced full recovery of both cellular and serological response parameters including IFN-gamma secretion and anti-spike antibody titers with strong neutralization capacities against wild type SARS-COV-2 and Delta. Surprisingly, even serological neutralization capacity against Omicron was detectable one month after second vaccination and four months before it had been first observed in South Africa. As a result, more than 90% of convalescent individuals exhibited detectable and 75% strong Omicron neutralization capacity after booster vaccination, compared with 72% and 46% of COVID-19-naïve individuals. Our results support the notion that broad and cross-reactive immune memory against SARS-CoV-2 including currently known VOCs can be established by booster vaccination with spike-based mRNA vaccines like BNT162b2, particularly in COVID-19-convalescent individuals of all ages. Nevertheless, especially in COVID-19-naïve individuals future variants escaping the memory immune response may require vaccine approaches such as inactivated whole virus vaccines, which include all antigenic components of the virus.